2022
DOI: 10.1111/syen.12521
|View full text |Cite
|
Sign up to set email alerts
|

Describing biodiversity in the genomics era: A new species of Nearctic Cynipidae gall wasp and its genome

Abstract: Gall wasps (Hymenoptera: Cynipidae) specializing on live oaks in the genus Quercus (subsection Virentes) are a relatively diverse and well‐studied community with 14 species described to date, albeit with incomplete information on their biology, life history and genetic structure. Incorporating an integrative taxonomic approach, we combine morphology, phenology, behaviour, genetics and genomics to describe a new species, Neuroterus valhalla sp. nov. The alternating generations of this species induce galls on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 137 publications
2
26
0
Order By: Relevance
“…As in several previous phylogenetic treatments of the Cynipini (Rokas et al 2003, Ács et al 2010, Ronquist et al 2015, Cooke 2018, Andersen et al 2021, Brandão-Dias et al 2022, several gall wasp genera, including Andricus, Callirhytis, Neuroterus, and Dryocosmus, were found to be either para-or polyphyletic in our tree topologies (Figures 1-4). Of the genera represented in the tree by more than three species, only three genera: Amphibolips, Acraspis, and Disholcaspis maintain monophyly, the latter only because of a recent revision (Melika et al 2021a) after Cooke (2018) had found Disholcaspis to be polyphyletic.…”
Section: Phylogeny and Biogeography Of Cynipinisupporting
confidence: 80%
See 3 more Smart Citations
“…As in several previous phylogenetic treatments of the Cynipini (Rokas et al 2003, Ács et al 2010, Ronquist et al 2015, Cooke 2018, Andersen et al 2021, Brandão-Dias et al 2022, several gall wasp genera, including Andricus, Callirhytis, Neuroterus, and Dryocosmus, were found to be either para-or polyphyletic in our tree topologies (Figures 1-4). Of the genera represented in the tree by more than three species, only three genera: Amphibolips, Acraspis, and Disholcaspis maintain monophyly, the latter only because of a recent revision (Melika et al 2021a) after Cooke (2018) had found Disholcaspis to be polyphyletic.…”
Section: Phylogeny and Biogeography Of Cynipinisupporting
confidence: 80%
“…Most recently, Brandão-Dias et al (2022) added additional data harvested from published Cynipini genomes to expand the Blaimer et al (2020) UCE gall wasp dataset. Though not the main focus of any of these studies, in all cases the resultant phylogenies appear to show the Palearctic fauna as being paraphyletic.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…2010, 2018). Rapid development and increased availability of tools designed to capture genomic DNA has led to increased use of genome-wide approaches to analysis of phylogenomics, biogeography, demography, host shifts, and tritrophic interactions of gall communities (Blaimer et al, 2020;Brandão-Dias et al, 2022, Bunnefeld et al, 2018Driscoe et al, 2019;Samacá-Sáenz et al, 2020;Walton et al, 2021;Zhang Y.M. et al, 2020).…”
Section: Introductionmentioning
confidence: 99%